The Mental Health of Palestinian Adolescents in the Jabalia Refugee Camp: A Longitudinal Review - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Jurnal Anestesi, 2025)
This longitudinal meta-review study aims to comprehensively examine the impact of protracted conflict on the mental health of Palestinian adolescents living under conditions of displacement in the Jabalia Refugee Camp by systematically integrating 47 longitudinal studies conducted between 2000–2023, involving a total of 12,483 adolescent participants. The synthesis reveals an exceptionally severe psychopathological burden, with PTSD prevalence reaching 73.8% (95% CI: 70.2–77.4%), depression 68.5% (95% CI: 65.1–71.9%), and anxiety 65.2% (95% CI: 61.8–68.6%), underscoring war-related trauma as the primary determinant of mental disorder vulnerability within this population. Multiple regression analyses identified direct exposure to violence (B=0.64, p<0.001) and the loss of family members (B=0.58, p<0.001) as the strongest predictors of psychological disorder development, accompanied by a significant decline in psychosocial functioning of 45.7% over five years (p<0.001). In contrast to earlier reports by Qouta et al. (2012), which documented PTSD prevalence at 54.2%, and Vostanis (2003), which reported depression rates of 49.3%, this meta-review demonstrates a sharp escalation of mental health disturbances following 2021. The primary novelty of this study lies in its identification of community-based resilience, whereby engagement in collective activities reduced the risk of mental disorders by 27.3% (p<0.01). These findings highlight the urgent necessity of strengthening community-oriented mental health interventions and ensuring sustained psychosocial support for adolescents living in conflict zones.